GAYA PENGASUHAN ORANG TUA, INTERAKSI SERTA KELEKATAN AYAH-REMAJA, DAN KEPUASAN AYAH - Krisnatuti, Diah; Putri, Husfani Adhariani (Jurnal Ilmu Keluarga dan Konsumen, 2012)
The aim of this research was to analyze the correlation among parenting styles, interaction and attachment of father-adolescence, and father’s satisfaction. This study involved 60 fathers, devided into 30 fathers with male children and 30 fathers with female children who aged 12-14 years. Data was analyzed by descriptive, independent sample t-test, and Pearson corellation. The result showed that mostly adolescent perceived their parents as democratic parenting style. Mostly, communication pattern between father and adolescent was conversation-orientation, while the communication type was consensual. The mean of father-adolescent interaction in a day was 0,47 hours for male and 0,64 hours for female adolescent. There was positive significant between democratic parenting style with communication pattern of conversation-orientation. Communication pattern of conversation-orientation that applied by fathers was positively related to the dimensions of trust in attachment of father-adolescent. Communication pattern of conformity-orientation that applied by fathers was negatively related to fathers’ satisfaction levels.